Altering the IgE binding capacity of king prawn (Litopenaeus Vannamei) tropomyosin through conformational changes induced by cold argon-plasma jet. (1st December 2019) - Ekezie, Flora-Glad Chizoba; Sun, Da-Wen; Cheng, Jun-Hu
Abstract: Tropomyosin (TM), a myofibrillar protein, is a major allergen in most crustaceans including king pawn ( Litopenaeus vannamei ). In this study, the structural modifications and allergenic response of TM in fresh king prawn as induced by cold argon plasma jet (CAPJ) were examined. The result showed that the level of α-helix structures declined as treatment time progressed, while the level of β-sheets and random coils increased. The free sulfhydryl groups decreased as CAPJ treatment progressed due to the formation of disulphide bonds while surface hydrophobicity increased until equilibrium values. In addition, after 15 min of plasma exposure, the maximum reduction recorded for IgE and IgG binding capacities were 17.6% and 26.87% respectively as revealed by ELISA test. These findings correlated with the occurrence of protein unfolding and denaturation, evident by complementary structural analyses conducted. The study indicates that non-thermal plasma maybe a promising tool for developing hypoallergenic food products.